Effects “in Vitro” of Some Cardiovascular Drugs and Other Agents on Human Platelet Aggregation - Sacchetti, G; Bellani, D; Montanari, C; Gibelli, A (Thrombosis and Haemostasis, 1973)
The in vitro effect of the following substances on human platelet aggregation is studied: K 4423 (a ß-blocking drug), isoproterenol, phentolamine, papaverine, methamidoline (a myolytic agent).None of these substances causes aggregation. All inhibit aggregation induced by ADP or noradrenaline, except for phentolamine, which is active only on noradrenaline- induced aggregation.Hypothesis on the mechanism of action of the compounds tested are proposed.